Guía de Inspección para la Supervisión de Hinca de Pilotes y Colocación de Concreto estructural en Puentes según la Norma INTE-ISO/IEC 17020:2000 - Parra-Rivera, Diego (Instituto Tecnológico de Costa Rica, 2013)
This work is based in the current deficiency existing in the National Roads Council's quality assurance inspection of newly built roadways. The objective of the project is to create an inspection procedure for deep foundations installations (pile driving) and placement of structural concrete, that allows for the evaluation of conformity with current technical specifications. The criterion from norm INTEISO/ IEC 17020:2000 were applied in order to meet with the quality standards required by the construction directive CR 2010. As a result, an inspection guide was obtained. This guide allows the evaluation of process conformity in a practical and efficient manner, through the use of inspection and control models, as well as specification verification lists.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción).Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2013.
Keywords: Procedimiento; Inspección; Acreditación; Normalización; Cimientos; Red vial